A hybrid relief procurement contract for humanitarian logistics. (November 2022) - Ghavamifar, Ali; Torabi, S. Ali; Moshtari, Mohammad
Highlights: Proposing a novel hybrid relief procurement contract. Incorporating the characteristics of QFC and option contract into a hybrid contract. Categorizing Iran's provinces according to multi-hazard risks. Applying the contract on a real case study and proposing several managerial insights. Abstract: This paper proposes a novel hybrid relief procurement contract in which the specific features of option contract and quantity flexible contract are used to coordinate the supply of a relief item between a supplier and a humanitarian organization. First, a mathematical statistics approach is used to categorize different provinces according to a multi-hazard risk approach. Then, the proposed contract is elaborated. Different managerial insights are derived from conducting several sensitivity analyses in our case study. The results reveal that using the proposed contract can significantly improve the procurement process by reducing the shortage and overstocking risks in humanitarian organizations.